2022
DOI: 10.3389/fonc.2022.892078
|View full text |Cite
|
Sign up to set email alerts
|

Determining Out-of-Field Doses and Second Cancer Risk From Proton Therapy in Young Patients—An Overview

Abstract: Proton therapy has the potential to provide survival and tumor control outcomes comparable and frequently superior to photon therapy. This has led to a significant concern in the medical physics community on the risk for the induction of second cancers in all patients and especially in younger patients, as they are considered more radiosensitive than adults and have an even longer expected lifetime after treatment. Thus, our purpose is to present an overview of the research carried out on the evaluation of out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
(126 reference statements)
0
8
0
Order By: Relevance
“…As discussed before, in terms of spot size, it is preferable to choose a position as close as possible to the patient. However, studies in passive scatter facilities have showed the decrease of organ doses by increasing the air gap 10 . A similar behavior is expected in the case of the RS and, therefore, an optimal configuration in terms of proton dose distribution within the target is unfavorable in terms of neutron production and thus unwanted dose deposition in organs at risk.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…As discussed before, in terms of spot size, it is preferable to choose a position as close as possible to the patient. However, studies in passive scatter facilities have showed the decrease of organ doses by increasing the air gap 10 . A similar behavior is expected in the case of the RS and, therefore, an optimal configuration in terms of proton dose distribution within the target is unfavorable in terms of neutron production and thus unwanted dose deposition in organs at risk.…”
Section: Introductionmentioning
confidence: 52%
“…The proton beam scored after the RS presented a component of higher energies in comparison to the NRS plan. Since the neutron production increases with proton energy, 10 these more energetic protons in the RS plan explain why doses due to the neutrons originated in the phantom are generally higher than in the NRS plan (as illustrated by the values of equivalent doses in organ in Table 1). Nevertheless, the more energetic protons are producing more high energy neutrons which are forward directed and not likely to contribute to doses to distant organs and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Proton therapy has gained increasing interest in past decades as it offers superior dose conformity and reduces the adverse effects on healthy tissues compared to photon radiotherapy 1 . The use of proton therapy has been shown to reduce the incidence of secondary cancers in long‐term survivors, making it a more favorable option especially for pediatric patients and patients with localized tumors 2–5 . Since 2014, the concept of FLASH therapy has emerged as a promising approach to greatly reduce the toxicity in radiotherapy treatments by delivering an ultra‐high dose rate (UHDR) of radiation exceeding 40 Gy/s 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…As long-term follow-up and prospective clinical studies are difficult to conduct, more consideration has been given to modelling studies to determine risk of SPC in children (for latest review see Romero-Expósito et al 8 and references within). Mathematical prediction of SPC can be somewhat contentious as parameters associated with increased risk are based on historically collected data from high irradiation incidents and adult populations.…”
Section: Introductionmentioning
confidence: 99%